[Rezension von: Lama Jabb: Oral and literary continuities in modern Tibetan literature] - Samuels, Jonathan (International journal of Asian studies, 2016)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS1479591416000139/resource/name/firstPage-S1479591416000139a.jpg